RELATIONSHIP BETWEEN CREATIVITY AND SELF-CONCEPT ON STUDENTS’ ACADEMIC ACHIEVEMENT IN BORNO STATE COLLEGE OF EDUCATION: IMPLICATIONS FOR COUNSELLING - Goni, U.; Tambawal, M. U. (Sokoto Educational Review, 2013)
This is a correlational study design to determine the relationship between creativity and self-concept on students' academic achievement in Colleges of Education in Borno State. The study set three research objectives and tested three research hypotheses. For the purpose of this study, two main approaches were used; cognitive approaches were applied to creativity while humanistic approaches were also applied to self-concept. The uniqueness of this study lies in the area where Xiaxia (1999) investigated gender differences in their examination of the relationship between creativity and academic achievement. While this study focuses on creativity and self-concept on students’ academic achievement, the target population for this study was 4,517 students who have registered in NCE awarding institutions in Borno State. Purposive sampling technique was used to select two Colleges of Education in Borno State, the stratified random sampling procedure was also employed to select 322 participants 186 students from 351 NCE III students’ from Kashim Ibrahim College o f Education, Maiduguri and 136 students from 210 NCE III students from Umar Ibn Ibrahim College of Education, Science and Technology, Bama. Students’ Creativity Test (SCT) and Students’ Self-concept Scale (SUSS) was used by the researchers. Pearson ‘r’ was used to test the hypotheses raised in this study. The results indicated a very low and positive relationship between creativity and self-concept among students of Colleges of Education, the results indicated a high and positive relationship between the two variables and the results also indicated a very high and positive relationship between the two variables. Based on the results obtained the following Counselling strategy are suggested; there is the need for counselling personnel to guide the students on how well they should improve their creativity and self-concept through enhancing the students ’ imaginative thinking and improvised their needs by the authority